ROLE OF INCISIONAL VACUUM THERAPY IN ENDOPROSTHETIC BONE RECONSTRUCTION SURGERY - ANDRÉ MATHIAS BAPTISTA; ANDRÉ FERRARI DE FRANÇA DE CAMARGO; MARCELO TADEU CAIERO; JOSÉ SAINT CLAIR DE SOUSA TORRES FILHO; JORGE HENRIQUE NARCISO; MARCELA ROCHA DIAS SILVA (Acta Ortopédica Brasileira, 2023)
ABSTRACT Reconstructive surgery with endoprostheses is the chosen method for treating bone malignancies. Postoperative infections are frequent complications, and their treatment involves prolonged hospital stays and antibiotic therapy. Among the advancements aimed at reducing the rate of postoperative infection, the use of incisional negative pressure therapy (iNPT) has shown promising results, with no reports in the literature regarding its use in patients with such conditions. Objective: To evaluate the effectiveness of iNPT in reducing postoperative complications in surgeries for resection of bone tumors associated with modular endoprosthesis reconstruction. Methods: Retrospective case series of 16 patients diagnosed with osteosarcoma, who underwent resection and reconstruction with endoprosthesis associated with iNPT during the postoperative period. Follow-up was performed for a period of six months, and the evaluated outcomes were the incidence of postoperative infection and complications of the surgical wound. Results: The use of iNPT for a postoperative period of seven days resulted in only three (18.7%) cases of postoperative infection. No cases of wound dehiscence, seroma formation, or hematoma at the surgical site were observed. Conclusion: The rate of surgical wound complications in our case series is lower than that reported in most of the literature, and iNPT appears to be an efficient way to reduce the rate of local complications in reconstructive surgeries with endoprosthesis after resection of bone malignancies. Level of Evidence III, Retrospective Study.